Cognitive Fatigue Influences Time-On-Task during Bodyweight Resistance Training Exercise - Head, James R.; Tenan, Matthew S.; Tweedell, Andrew J.; Price, Thomas F.; LaFiandra, Michael E.; Helton, William S. (Frontiers in Physiology, 2016)
Prior investigations have shown measurable performance impairments on continuous physical performance tasks when preceded by a cognitively fatiguing task. However, the effect of cognitive fatigue on bodyweight resistance training exercise task performance is unknown. In the current investigation 18 amateur athletes completed a full body exercise task preceded by either a cognitive fatiguing or control intervention. In a randomized repeated measure design, each participant completed the same exercise task preceded by a 52 minute cognitively fatiguing intervention (vigilance) or control intervention (video). Data collection sessions were separated by 1 week. Participants rated the fatigue intervention as being significantly more mentally demanding than the control intervention (p < .001). Additionally, participants self-reported significantly greater energetic arousal for cognitively fatiguing task (p = .02). Cognitive fatigue did not significantly impact number of repetitions completed during the exercise task (p = .77); however, when cognitively fatigued, participants had decreased percent time-on-task (57%) relative to the no fatigue condition (60%) (p = .04). RPE significantly changed over time (p < .001), but failed to show significant differences between the cognitive fatigue intervention and control intervention (p > .05). There was no statistical difference for heart rate or metabolic expenditure as a function of fatigue intervention during exercise. Cognitively fatigued athletes have decreased time-on-task in bodyweight resistance training exercise tasks.